2017
DOI: 10.1016/j.jempfin.2016.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Return expectations and risk aversion heterogeneity in household portfolios

Abstract: We develop a structural econometric model to elicit household-specific expectations about future financial asset returns and risk attitudes by using data on observed portfolio holdings and self-assessed willingness to bear financial risk. Our framework assumes that household portfolios are subject to short-selling constraints in stocks and bonds, and that financial investment decisions are taken conditional on real estate and business wealth. We derive an explicit solution for the model, and estimate its param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…According to Grable and Lytton (1999) and Hallahan et al (2004), financial risk tolerance can be measured using subjective judgments. In this study, the measurement of financial risk tolerance adapted a statement by Bucciol et al (2017), which reflects a person's perception of a willingness to take possible losses or opportunities to gain profits on the amount of money invested. However, according to Grable and Lytton (1999), the appropriate measurement for financial risk tolerance is to use subjective measurements that are specifically formulated using various scenarios and situations.…”
Section: Resultsmentioning
confidence: 99%
“…According to Grable and Lytton (1999) and Hallahan et al (2004), financial risk tolerance can be measured using subjective judgments. In this study, the measurement of financial risk tolerance adapted a statement by Bucciol et al (2017), which reflects a person's perception of a willingness to take possible losses or opportunities to gain profits on the amount of money invested. However, according to Grable and Lytton (1999), the appropriate measurement for financial risk tolerance is to use subjective measurements that are specifically formulated using various scenarios and situations.…”
Section: Resultsmentioning
confidence: 99%
“…Retirement is a crucial life stage that impacts household asset decisions and has the potential to affect participants’ willingness to take risks in the financial markets. According to several studies, investors who are retired are more risk-averse ( 47 ). Because of this, households headed by people over 60 tend to be naturally risk cautious and prefer low-risk financial products, which are less influenced by health risks and medical insurance.…”
Section: Theoretical Analysis and Research Hypothesismentioning
confidence: 99%
“…Education level also affects intergenerational differences in family income (Liu & Faye, 2021); there is a large difference in choices related to risky financial assets between married and single people. Addoum et al (2017) found that the investments in stocks of retired couples tended to decrease significantly, while those of single people did not change significantly; it was also shown that men are more willing to assume risks than women, and their investment-error tolerance rate is higher (Bucciol et al, 2017;Guiso & Zaccaria, 2021). Mumtaz and Smith (2021) found that different demographics engage in different behaviours; regional financial development can promote investment by families in risky assets by reducing market friction on the supply side and improving families' financial literacy on the demand side (Lu et al, 2019).…”
Section: Data and Variablesmentioning
confidence: 99%